Fluid overload–associated large B-cell lymphoma with primary biliary cirrhosis: A case report - Wang, Huan; Zhang, Quan; Liu, Qin; Wu, Xian; Ma, Ke (Frontiers in Oncology, 2023)
The 5th edition of World Health Organization (WHO) Classification of Haematolymphoid Tumours (WHO-HAEM5) is characterized by its hierarchical system for classification and novel entities/types. Considering the significant discrepancy in clinical manifestations and prognosis, fluid overload-associated large B-cell lymphoma (FOALBCL) has been a new addition to WHO-HAEM5, being distinct from traditional diagnosis of primary effusion lymphoma (PEL). In this manuscript, we report a patient who was diagnosed with fluid overload-associated large B-cell lymphoma that a novel entity introduced in the WHO-HAEM5. It is an instance of successful application of the updated WHO-HAEM5, and indicates that the ′Blue Book′ could confer convenience and benefits on both patients and clinicians. Moreover, the patient combined primary biliary cirrhosis (PBC), which is a relatively rare condition compared to the underlying medical condition of viral cirrhosis. Due to atypical clinical symptoms and invasive biopsy of lymphoma, sometimes diagnoses might be undesired, which eventually lead to a poor prognosis. With this case report, it reminds not just hematologists but also other specialists to pay attention to updates and revisions of classifications of lymphoma.